2010
DOI: 10.1007/s00253-009-2431-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of sustainable chemistry to produce an acyl amino acid surfactant

Abstract: Surfactants find wide commercial use as foaming agents, emulsifiers, and dispersants. Currently, surfactants are produced from petroleum, or from seed oils such as palm or coconut oil. Due to concerns with CO(2) emissions and the need to protect rainforests, there is a growing necessity to manufacture these chemicals using sustainable resources In this report, we describe the engineering of a native nonribosomal peptide synthetase pathway (i.e., surfactin synthetase), to generate a Bacillus strain that synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 27 publications
2
65
0
1
Order By: Relevance
“…[8,38]. The global production of surfactants was estimated to 12 M tons/year in 2008 with a growth rate of 2%–3% per year [39,40]. …”
Section: Surfactantsmentioning
confidence: 99%
“…[8,38]. The global production of surfactants was estimated to 12 M tons/year in 2008 with a growth rate of 2%–3% per year [39,40]. …”
Section: Surfactantsmentioning
confidence: 99%
“…It has been reported that the worldwide production of synthetic surfactants is over 15 million tons per year ( Van-Bogaert et al 2007 ) that are employed in different industrial sectors ranging from food processing, pharmaceutical, cosmetics, detergent production, environmental cleanup (bioremediation) and enhanced oil recovery. According to Reznik et al ( 2010 ), the worldwide production of synthetic surfactants per annum was 13 million tons in 2008, increased by 2 % in 2009 resulting to annual turnover of US$ 2,433 billion. The market was then expected to experience a continuous growth by 28 % from 2009 to 2012 and thereafter increase approximately by 3.5-4 %.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants have widespread importance for applications in diverse fields such as the detergent, personal care, textile, petrochemical, pharmaceutical and electronic industries for performing the desired function of cleaning, wetting, softening, foaming, emulsifying, etc. [1][2][3][4][5][6][7][8][9]. In recent years, interest has been generated to explore new types of surfactants having antimicrobial properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%